Clinical Sequelae From Overfeeding in Enterally Fed Critically Ill Adults: Where Is the Evidence?. Issue 6 (17th November 2019) - Chapple, Lee‐anne S.; Weinel, Luke; Ridley, Emma J.; Jones, Daryl; Chapman, Marianne J.; Peake, Sandra L.
Abstract: Enteral energy delivery above requirements (overfeeding) is believed to cause adverse effects during critical illness, but the literature supporting this is limited. We aimed to quantify the reported frequency and clinical sequelae of energy overfeeding with enterally delivered nutrition in critically ill adult patients. A systematic search of MEDLINE, EMBASE, and CINAHL from conception to November 28, 2018, identified clinical studies of nutrition interventions in enterally fed critically ill adults that reported overfeeding in 1 or more study arms. Overfeeding was defined as energy delivery > 2000 kcal/d, > 25 kcal/kg/d, or ≥ 110% of energy prescription. Data were extracted on methodology, demographics, prescribed and delivered nutrition, clinical variables, and predefined outcomes. Cochrane "Risk of Bias" tool was used to assess the quality of randomized controlled trials (RCTs). Eighteen studies were included, of which 10 were randomized (n = 4386 patients) and 8 were nonrandomized (n = 223). Only 4 studies reported a separation in energy delivery between treatment groups whereby 1 arm met the definition of overfeeding, which reported no between‐group differences in mortality, infectious complications, or ventilatory support. Overfeeding was associated with increased insulin administration (median 3 [interquartile range: 0–41.8] vs 0 [0–30.6] units/d) and upper‐gastrointestinal intolerance in 1 large RCT and with duration of antimicrobial therapy in a small RCT. There are limited high‐quality data to determine the impact of energy overfeeding of critically ill patients by the enteral route; however, based on available evidence, overfeeding does not appear to affect mortality or other important clinical outcomes.